TANGGUNG JAWAB HUKUM EMITEN TERHADAP PRAKTEK INSIDER TRADING DI PASAR MODAL MENURUT UNDANG-UNDANG NO 8 TAHUN 1995 - WISUDAWAN, I GUSTI AGUNG; ISMAIL, HJ. SUMIATI; BUDIARTO, AGUS (GANEC SWARA, 2018)
Practice Insider Trading is a fraudulent practices, because the principle of openness to shared or distributed to the public is information that is material or facts material that is information or important facts and relevant about events, occurrences, or facts that may affect the price of securities on the Stock Exchange and / or the decision of the financier, the prospective investor or any other party concerned with such information or facts. This practice is very difficult to prove. Issuers negligence for allowing the practice of insider trading by the issuer itself, it is thus the Issuer should be accountable and penalized adminitratif law. This is done so that Issuers really keep their trading in the capital market. In addition it is very urgent revision of the Capital Market Law to be done in order to provide legal certainty and provide a deterrent effect to the perpetrators of Insider Trading and give legal protection for parties working in the capital market.